Islamic Republic of Afghanistan : Report on Observance of Standards and Codes: FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2011)
This report is a detailed assessment on antimoney laundering (AML) and combating the financing of terrorism (CFT) for the Islamic Republic of Afghanistan. Afghanistan is one of the poorest countries in the world, and it is still at an early stage of developing its legal and institutional framework. Even though measures have been taken to fight crime and to lay the foundations for an AML/CFT regime, current efforts are not sufficient to deal with high risk of money laundering and terrorist financing in the country.